Diseño de vestidos de alta gala con aplicación de técnicas de bordado manual - Ocaña Lara, Mariela Elizabeth (2020)
In this project, the implementation of new designs of high gala dresses is carried out, highlighting the application of manual embroidery techniques studied and put into practice, resulting in the creation of a design proposal with a high level of sophistication. the same time, it aims to develop high gala costumes with the application of manual embroidery techniques, for which a bibliographic compilation was made for later analysis, the tastes and preferences of the target group were also determined as regards high gala refers, as well as the frequency of purchase of the aforementioned suits. Finally, the data obtained from this quantitative study was analyzed because the preferences of the respondents are valued in terms of materials and details, in order to have tools to structure several design proposals that are consistent with the requirements of the market. The information obtained and collected provided the possibility of developing High Gala Costume Design with the application of manual embroidery techniques, which shows that the use of suitable materials for high gala dresses is a differentiating tool, in this type of What you are looking for is to highlight the beauty of women in different types of events.